Apert Syndrome: A Case Report - Shahin Mafinejad; Hojat Ehteshammanesh; Ghasem Bayani; Hosein Mahmoodzade (Mashhad University of Medical Sciences, 2022)
Background: Primary craniosynostosis is a form of premature fusion of the cranial sutures, which commonly occurs prenatally. The condition appears in both syndromic and nonsyndromic forms.Case report: The cause of most cases of primary craniosynostosis are unknown, with genetic syndromes explaining 10%-20% of cases. The most prevalent syndromes associated with primary craniosynostosis are Crouzon, Apert, and Pfeiffer. Scaphocephaly is the most typical form of craniosynostosis that occurs due to premature closure of the sagittal suture. Frontal plagiocephaly is another form of this condition that is caused by the premature fusion of a sphenofrontal or coronal suture. The suture line palpation at birth usually exhibits a bony ridge. In these case, head CT or skull radiograph may be prescribed. Some genetic types of craniosynostosis are triggered by FGFR1, TWIST, FGFR2, or FGFR3 mutations.Conclusion: A rare congenital condition, Apert syndrome is associated with craniosynostosis and severe symmetrical syndactyly of the feet and hands. In this case study, the goal has been to present a newborn with all characteristics of a classical Apert syndrome.